LOCALIZATION OF DISLOCATION CREEP IN THE LOWER MANTLE: IMPLICATIONS FOR THE ORIGIN OF SEISMIC ANISOTROPY - McNamara A.K.; Karato S.I.; van Keken P.E. (My University, 2001)
Recent seismological observations reveal the presence of seismic anisotropy in localized regions at the base of the mantle within an otherwise isotropic lower mantle. These regions can be placed in a tectonic context, corresponding to locations of paleosubduction and plume upwelling. This project works toward determining whether the observed seismic anisotropy may be explained by the development of a mineral fabric by lattice-preferred orientation (LPO). Numerical modeling is used to explore whether the conditions at the base of upwelling and downwelling regions are consistent with those required for fabric development. Specifically, we examine whether dislocation creep dominates these regions within a background mantle that flows primarily by diffusion creep. The key to our study is the use of a composite rheology that includes both mechanisms of diffusion and dislocation creep and is based on mineral physics experiments. Results show that it is possible to produce a localization of dislocation creep near slabs within a background mantle dominated by diffusion creep. In contrast, upwelling regions are characterized by a domination of diffusion creep. These results indicate that LPO may be the cause of lowermost mantle seismic anisotropy near paleoslabs, but other mechanisms such as shape-preferred orientation may be required to produce the anisotropy observed near upwellings.
Keywords: MANTLE; CONVECTION; ANISOTROPY; DISLOCATION CREEP; CORE-MANTLE BOUNDARY